2018
DOI: 10.2147/cia.s158501
|View full text |Cite
|
Sign up to set email alerts
|

Preferences and attitudes of older adults of Bialystok, Poland toward the use of over-the-counter drugs

Abstract: PurposeThe aim of the study was to assess preferences and attitudes toward the use of over-the-counter (OTC) drugs among residents of Bialystok aged 60 or older.Patients and methodsThe study included 170 people, inhabitants of Bialystok aged over 60: 85 students of the University of a Healthy Senior and the University of Psychogeriatric Prophylaxis, and 85 students of the University of the Third Age in Bialystok. The study made use of a diagnostic survey conducted via a questionnaire prepared by the authors.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
(45 reference statements)
1
10
0
2
Order By: Relevance
“…Older individuals are one of the groups with the highest rates of emergency department (ED) visits [2]. Challenges that impact ED care for this patient population include multiple morbidities, atypical symptoms, polypharmacy, and drug interactions, as well as misuse of prescription and over-the-counter medications [3][4][5]. Additionally, older adults may present with functional disabilities, impaired cognition, and communication problems [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Older individuals are one of the groups with the highest rates of emergency department (ED) visits [2]. Challenges that impact ED care for this patient population include multiple morbidities, atypical symptoms, polypharmacy, and drug interactions, as well as misuse of prescription and over-the-counter medications [3][4][5]. Additionally, older adults may present with functional disabilities, impaired cognition, and communication problems [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…11 In another study on preferences and attitudes toward the use of OTC drugs, authors have concluded that many OTC drug consumers did not always demonstrate responsible attitudes toward using these preparations, including informing themselves on possible effects on human health in case of high doses. 17 In this study also, vitamins were the most commonly used OTC preparations. Importance of disclosing data on usage of OTC drugs in medical charts has been emphasized by other authors, whereas lack of information is associated with a risk of overlooking interactions with prescribed drugs, especially in elderly patients.…”
Section: Discussionmentioning
confidence: 75%
“…Wawruch et al described that elderly patients who considered that the use of several drugs could increase the risk of ADRs were less probable to consider OTC drugs as safe [46]. Irresponsible use of OTC drugs in this age group was previously observed and the limitation of OTC drug availability to pharmacies only was proposed [47]. Use of OTC analgesics, which were excluded from this study, has been associated with increased ADR risk and our results reflect the need to use all OTC drugs with caution in the elderly population [48].…”
Section: Discussionmentioning
confidence: 99%